The Design and Fabrication of Waterwheels with System Floating Pontoon - Fatahul Arifin; Hadi Sutanto; Isdaryanto Iskandar; Ronald Sukwadi (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
The use of fossil energy is currently starting to be slightly reduced by the government, and at this time the government is also starting to look at renewable energy as alternative energy, just as energy, solar, wind, biomass, and water. One of the utilization of water energy for the use of electrical energy is with a waterwheel. In this study, a pontoon-type water wheel was designed, where the ratio of rotation of the wheel to the rotation of the generator rotor was 1: 4. The dimensions of the water wheel designed and made were with a pontoon width of 1080 mm x 2000 mm x 15 mm, and the diameter of the water wheel is 1200 mm, which can be generated by a generator of 1 watt.